Effects of modified biochars on the shifts of short-chain fatty acid profile, iron reduction, and bacterial community in paddy soil. Issue 12 (11th November 2022) - Liu, Qian; Zhong, Linrui; Hu, Yingju; Fu, Leiling; Hu, Xingxin; Gu, Yujing; Xie, Qingqing; Liang, Fangyi; Liu, Qi; Lu, Yue
Abstract: Biochar is well known as an effective means for soil amendment, and modification on biochar with different methods could improve the benefits for environmental remediation. In this study, two modified biochars were generated with nitric acid (NBC) and hydrogen peroxide (OBC) pretreatment, and a control biochar was produced after washing with deionized water (WBC). The dynamics of short-chain fatty acids (SCFAs), iron concentration and bacterial community in rice paddy soil amended with different biochars or without adding biochar (CK) were studied during 70 days of anaerobic incubation. Compared to CK treatment, the accumulation of SCFAs was largely inhibited by the amendment of biochars. Besides, OBC and WBC increased the accumulation of Fe(II) at the initial stage of incubation. Via 16S rRNA gene sequencing, modified biochars caused significant response of bacterial community in comparison to WBC at Day 0–1, and three biochars favored bacterial α-diversity in the paddy soil at the end of the incubation. Interestingly, positive and negative correlations between NBC and several bacteria taxa (e.g. Geobacter, Fonticella and Clostridium ) were observed. The study revealed that modified biochars had significant effects on the shifts of SCFAs, Fe(III) reduction and bacterial diversity, which provides fundamental information for future application of modified biochars in rice cropping ecosystem. Abstract : Biochar pretreated with different modifiers has distinct effects on SCFA profiles, Fe(III)-reduction and bacterial diversity of paddy soil.